Comments on recent International Ethics Standards Board for Accountants Exposure Drafts regarding sustainability assurance and the use of external experts - Hay D; Harding N; Botica Redmayne N; Khan J; Singh H; Sultana N; You J (John Wiley and Sons Australia, Ltd on behalf of Accounting and Finance Association of Australia and New Zealand, 2024)
We commend the International Ethics Standards Board for Accountants for the initiative in releasing the two related Exposure Drafts regarding sustainability assurance and the use of external experts. There is a need for assurance over sustainability information, and for that assurance to be provided by professional people who have the appropriate guidance on ethical issues. There is an increasing need to draw on the work of experts and an increasing possibility that inappropriate reliance on that work by professional accountants and sustainability assurance practitioners may threaten compliance with the fundamental principles of the code of ethics.
Keywords: assurance; audit; ethics; profession-agnostic; sustainability